MECHANISMS OF INNOVATIVE DEVELOPMENT OF MARKETING SYSTEMS: ESSENCE, STRUCTURE, AND DIRECTIONS OF TRANSFORMATION - GARAFONOVA, Olga; DVORSKYI, Vladyslav; PONOMARENKO, Mykola; Verkhusha, OLEKSANDR (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the essence of innovative marketing as a modernized model of organizing marketing activities, oriented towards digitalization, analytical technologies, and advanced communication approaches. It is established that the key elements of innovative marketing include systematic study of consumer needs, the formation of a unique value proposition, the implementation of modern digital tools, and the use of artificial intelligence. These approaches contribute to ensuring a sustainable competitive advantage for enterprises. The importance of integrating digital platforms, automated analysis systems, and adaptive management tools in a dynamic external environment is emphasized. Particular attention is paid to the role of personalized consumer experience as a means of building long-term brand loyalty. It is stated that innovation marketing performs not only a communication function but also evolves into a conceptual model of innovative entrepreneurship. A dual approach to innovation marketing is outlined—both as a mechanism for identifying prospects and as a tool for supporting the innovation cycle. The article highlights innovations in the field of marketing, including new methods of research, segmentation, communication, repositioning, distribution, and adaptation of the product life cycle. It is noted that the current competitive landscape demands rapid implementation of innovative tools for market monitoring and responsiveness to changing demands. The effectiveness of the innovative approach is confirmed by examples of successful use of digital technologies by leading companies. Emphasis is placed on the necessity of strategically rethinking the role of innovation marketing in the development of business structures. It is noted that innovation marketing performs conceptual, instrumental, and coordinating functions. Innovative marketing is defined as a key mechanism for adaptation to digital transformation. The need to form a new marketing culture focused on proactively creating competitive advantages is substantiated.
Keywords: innovative marketing; marketing of innovations; strategic management; digital technologies; marketing systems; transformation